Association Between Anticholinergic Drug Burden and Adequacy of Enteral Nutrition in Critically Ill, Mechanically Ventilated Pediatric Patients. Issue 12 (December 2021) - Martinez, Enid E.; Dang, Hongxing; Franks, Jennifer; Callif, Charles G.; Tasker, Robert C.; Madden, Kate; Mehta, Nilesh M.
Abstract : OBJECTIVES: Enteral nutrition delivery is limited by intolerance and interruptions in critically ill children. Anticholinergic properties of frequently administered medications may contribute to altered gastric motility and enteral nutrition intolerance in this population. We examined the association between the anticholinergic burden of administered medications using the Anticholinergic Drug Scale and adequacy of enteral nutrition delivery. DESIGN: Secondary analysis of data from a previously characterized PICU cohort. SETTING: Multidisciplinary PICU in a quaternary academic medical center. PATIENTS: Younger than or equal to 18 years, on mechanical ventilation and received enteral nutrition within the first 3 days of PICU admission. MEASUREMENTS AND MAIN RESULTS: Daily Anticholinergic Drug Scale score, demographic data, and clinical data were obtained from the primary study. Percent enteral energy adequacy ([kcal delivered ÷ kcal prescribed] × 100) during the first 3 days of PICU admission was calculated. Forty-two patients received enteral nutrition, with median age (interquartile range) 5 years (1.09–12.54 yr), and 62% were male. Median Anticholinergic Drug Scale score was inversely correlated with energy adequacy, with a median 9% decline in energy adequacy per 1-point increase in Anticholinergic Drug Scale score (coefficient, –9.3; 95% CI, –13.43 to –5.27; R 2 = 0.35; p < 0.0001). Median hours of enteral nutrition interruptions directly correlated with Anticholinergic Drug Scale score (coefficient, 1.5; 95% CI, 0.531–2.54; R 2 = 0.19; p = 0.004). Severity score was greater in patients with less than or equal to 25% enteral energy adequacy and directly correlated with median Anticholinergic Drug Scale score. CONCLUSIONS: Anticholinergic burden from medications administered in the PICU is a potentially modifiable factor for suboptimal enteral nutrition delivery.